The Place of Psychology in the Area of Occupational Health and Safety: A Descriptive Comparison between the Turkish and Englih OHS Literatures - Seydahmet Ercan; Samet Çelik (Psikoloji Çalışmaları)
It is evident that we need to achieve immediate improvements in occupational health and safety (OHS) in Turkey considering the statistics provided by the International Labor Organization and the numerous tragic work-accidents (e.g., Soma mining accident). All concerned parties such as the Social Security Institution and employers’ associations need to fulfill their responsibilities by engaging in self-criticism. They must likewise develop suggestions to achieve such immediate improvements. Therefore, the academic society should contribute to the desired improvements in OHS by producing up-to-date, theoretical, and applicable knowledge. First, the Turkish OHS literature was examined to evaluate the academic society’s contribution. Second, the most frequently cited Turkish and English OHS articles were compared to highlight the main differences in Turkish and English OHS literature. Upon analyzing the Turkish OHS literature, the results indicated that the number of Turkish OHS related articles was inadequate. Moreover, the contributions of social and behavioral scientists to this domain was not sufficient. Furthermore, important OHS variables such as safety climate and safety culture were not studied enough, studies mostly used descriptive analysis, and there was a lack of hypothesis testing. Comparing Turkish and English OHS articles, the results indicated that the first authors of the English articles were mostly psychologists and the first authors of the Turkish articles were mostly engineers. Moreover, the English articles included more hypothesis testing. The Turkish articles included mostly descriptive analyses, while the English articles included mostly predictive analyses. The English articles likewise mostly included the safety climate as a predictive variable and health and wellbeing and injury and accidents as criterion variables. Based on these findings, Turkish researchers who study OHS should focus on studying variables directly related to safety behavior and safety intensions. They should produce applied knowledge by conducting predictive rather than descriptive analyses. Also, they need to consider taking a holistic perspective by incorporating the results obtained by different scientific areas of study. Following these suggestions, a more profound contribution of psychology to OHS literature is required.